Numerical prediction of impact damage in thick fabric composite laminates - Hoorn, N. van; Turteltaub S.R.; Kassapoglou, C.; Brink, W.M. van den (Elsevier, 2025)
A simulation methodology for assessing the damage in thick fabric Carbon Fibre Reinforced Polymer (CFRP) composite laminates under low- and high-velocity impacts is presented. It encompasses steps for calibration, verification, and validation of the elastic and fracture material properties as well as determination of model parameters for the numerical simulations. Damage is modelled using a discrete fracture approach with cohesive interface elements that capture individual cracks occurring in and between plies. For computational efficiency, the method is implemented in a two-dimensional (2D) axi-symmetric model. Results from double-cantilever beam, end-notched flexure, and quasi-static indentation experiments align well with numerical simulations and serve to calibrate and verify the implementation of the discrete fracture approach. The methodology is extended to dynamic impact analysis to predict damage mechanisms, force–displacement histories, and is validated using test results. This methodology combines meaningful insight in the failure mechanisms with a manageable computational effort, achieving a factor 50 improvement compared to a benchmark. A parametric analysis summarised in failure maps relates damage mechanisms to impact energy, mass, and laminate thickness. The proposed methodology strikes a balance between computational efficiency and accuracy, making it a valuable tool for optimum design and certification of thick CFRP composite laminates under impact.